TEACHER’S ROLE AS A FACILITATOR TO ENHANCE EFL STUDENTS’ SPEAKING SKILLS FOR GRADE XI AT SMA PAB 4 SAMPALI - Zuhana Syahfitri Siregar; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
The research focuses on the role of the teacher as a facilitator.The objective ofresearch was to know what are the characteristics of teacher’s role as a facilitatorto enhance EFL students’ speaking skill. This study was conducted at SMA PAB 4Sampali, Medan which the sample was the twenty five students and an Englishteacher at grade XI that had been selected by doing an observation and deliveringquestionnaire based on the characteristics of teacher’s role as a facilitator. Themethod for this research was qualitative descriptive. The data was collected bydistributing the questionnaire and doing an observation during the learning process.The results showed that the teacher completely fulfill the characteristics of teacher’srole as a facilitator.It is because the students dominantly choose strongly agree inthree characteristics and agree in five characteristics, that are Partnership (92%),Participant (96%), Knowledge available (84%), Open learning (84), and also Widerhorizon (60%).It was also found that the students choose that they are strongly agreein three caharacteristics, that are Focuses on learning (76%), Studentscentered(68%), and Sharing (68%).Meanwhile, the teacher can not play twocharacteristics, because the students dominantly choose disagree in Focus onIndividual Learning Needs (92%) and Let Students Set Parameter (68%).During thelearning process confirmed that the teacher was able to play a role as a facilitator.Itcan be seen from ten characteristics, the teacher had eight characteristics as afacilitator. However, it is so important for the teacher to have the characteristics asa facilitator in supporting students to enhance their speaking skill.